Characteristics of the Problems of Socio-Economic Development in the Conditions of Digital Economy - Мединська Тетяна Володимирівна; Lesia Sai; Oleksandr Akimkin; Liudmyla Kruchak; Tetiana Doroshenko (International Journal of Computer Science and Network Security, 2022)
The main purpose of the study is to determine the main aspects of the problem of socio-economic development in the conditions of the digital economy. The post-industrial era is characterized by the development of the electronic environment and the transition to an information civilization. In this regard, the developed countries of the world pay considerable attention to the development of the digital economy. However, there are a significant number of problems associated with this process. The country cannot be successful in the development of the digital economy in the absence of the necessary legal framework, an economic development strategy based on digital technologies. The research methodology involves the use of several theoretical methods for analyzing and synthesizing information. As a result of the study, the key problems of socio-economic development in the digital economy were characterized.
International Journal of Computer Science and Network Security. Vol. 22 No. 2, 2022, pp. 297-303
Keywords: Socio-Economic Development; economy; digital; digital economy